2020
DOI: 10.1111/oik.07431
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific trait variation in personality‐related movement behavior promotes coexistence

Abstract: Movement behavior is an essential element of fundamental ecological processes such as competition and predation. Although intraspecific trait variation (ITV) in movement behaviors is pervasive, its consequences for ecological community dynamics are still not fully understood. Using a newly developed individual-based model, we analyzed how given and constant ITVs in foraging movement affect differences in foraging efficiencies between species competing for common resources under various resource distributions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Temporal fluctuations in population density as a source of trait variation may have some vital implications for ecological research, as consequences of trait variation scale up to the community level (Bolnick et al 2011;Sih et al 2012;Violle et al 2012;Wolf and Weissing 2012), e.g. by affecting coexistence mechanisms (Hart et al 2016;Banitz 2019;Crawford et al 2019;Milles et al 2020) or mobile link functions (Brehm et al 2019;Schlägel et al 2020;Shaw 2020).…”
Section: Relation Between the Degree Of Phenotypic Variation And Pace Of Life (H2)mentioning
confidence: 99%
“…Temporal fluctuations in population density as a source of trait variation may have some vital implications for ecological research, as consequences of trait variation scale up to the community level (Bolnick et al 2011;Sih et al 2012;Violle et al 2012;Wolf and Weissing 2012), e.g. by affecting coexistence mechanisms (Hart et al 2016;Banitz 2019;Crawford et al 2019;Milles et al 2020) or mobile link functions (Brehm et al 2019;Schlägel et al 2020;Shaw 2020).…”
Section: Relation Between the Degree Of Phenotypic Variation And Pace Of Life (H2)mentioning
confidence: 99%
“…We do this because ITV usually affects relative fitness independently of which species has the fitness advantage without ITV. We reserve the term equalizing for a few particular studies where the impact of ITV depends on fitness differences without ITV (Crawford et al 2019, Milles et al 2020.…”
Section: Niche Traits and Hierarchical Traitsmentioning
confidence: 99%
“…However, using a form of the Hart et al model, with the addition of spatial environmental heterogeneity, Uriarte and Menge (2018) found that ITV sometimes (but not always) promoted coexistence amongst species that partitioned habitat. Some studies found that increasing ITV for all species helped coexistence (Crawford et al 2019, Milles et al 2020, while others found that it harmed coexistence (Courbaud et al 2012, Barabás and D'Andrea 2016, Stump et al 2020. Several studies have found that increasing ITV in one species promotes coexistence while increasing ITV in the other undermines coexistence; however, even then there are inconsistencies: in some cases, coexistence is promoted if the weaker species has higher ITV (Lichstein et al 2007), in others, either species can be the high-ITV species D'Andrea 2016, Gomes et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…S1.1). Similar algorithms are used throughout the literature to simulate landscapes with different degrees of patchiness of resources (Fahrig 1998;Milles et al 2020).…”
Section: Rationalementioning
confidence: 99%